The influence of temperature on the sensitivity of a SAW gas sensor with a thin layer of lead phthalocyanine - URBAŃCZYK, M. (Archives of Acoustics, 1997)
The paper deals with experimental investigations concerning theinfluence of temperature on the sensitivity of a SAW sensor with a thinlayer of lead phthalocyanine (PbPc) to NO2 molecules in the air.Measurements have been carried out with a dual delay line systemproviding simultaneously a survey of the differential frequency,Δf, and the measuring frequency, f. In all cases the measuredfrequency, f, was increased, whereas the changes in the difference offrequency, Δf, were negative as a result of the interactionwith NO2 molecules. All the experiments have been made at the sameconditions, i.e., with the same PbPc layer of a 310 nm thickness, at40ppm NO2 in air and at a constant gas flow rate of 100 ml/min.In the range 30-60oC, the sensitivity increased almostlinearly with temperature a constant rate of0.13-0.15 kHz/oC.